Paeonol ameliorates ferroptosis and inflammation in chondrocytes through AMPK/Nrf2/GPX4 pathway - Gong, Shuwei; Lang, Shuang; Jiang, Xuesheng; Li, Xiongfeng (Frontiers in Pharmacology, 2025)
IntroductionChondrocyte ferroptosis is an important component of the pathogenesis of osteoarthritis. Paeonol, the main pharmacologically active ingredient of the Paeonia suffruticosa Andrews, is a natural radical scavenger with potent biological activities, including antioxidant, anti-inflammatory, and cartilage protection effects. However, the molecular mechanisms underlying its role in regulating chondrocytes ferroptosis remain unclear.MethodsTo investigate the effect of paeonol on ferroptosis and inflammation of chondrocytes through interleukin-1β (IL-1β), the proliferation activity, lipid peroxidation level, endogenous antioxidant capacity, and mitochondrial membrane potential of chondrocytes were evaluated in detail. Intracellular ferrous ion concentration was detected by FerroOrange fluorescent probe staining. Western blotting and immunofluorescence staining were used to detect biomarker proteins of ferroptosis, inflammation, and AMPK/Nrf2/GPX4 signaling pathway proteins.ResultsThe results showed that paeonol significantly depressed IL-1β-induced ferroptosis and inflammation in chondrocytes. Specifically, paeonol protects cell viability, reduces lipid peroxidation damage, maintains mitochondrial function, and inhibits pro-ferroptosis and pro-inflammation biomarker proteins. In addition, the anti-inflammatory ability of paeonol was partially inhibited after the addition of ferroptosis agonist erastin, suggesting that paeonol protects against inflammatory injury in part by inhibiting ferroptosis. Further studies showed that paeonol activated AMPK phosphorylation and promoted Nrf2 nuclear translocation and Keap1 degradation. Finally, the AMPK-Nrf2-GPX4 signaling pathway was confirmed to be the underlying mechanism of paeonol against ferroptosis by the simultaneous use of the AMPK agonist and Nrf2 inhibitor.ConclusionThese results indicate that paeonol significantly inhibits IL-1β-induced ferroptosis and inflammation in chondrocytes, and the underlying mechanism of paeonol against ferroptosis is partly through the AMPK/Nrf2/GPX4 axis.